Leibniz a contribution to the archaeology of power. - Connelly, Stephen James (Encounters in law and philosophy., 2021)
Drawing on thinkers as diverse as Aristotle, Aquinas, Duns Scotus, Grotius, Husserl and Deleuze, Connelly traces Leibniz's conceptualisation of power through its applications in his legal texts, revealing that Leibniz in fact reconceptualises power under a new name: the state space.